Increasing Revenues for India Post through Expanding Channeling of Financial Services - World Bank (Washington, DC, 2013)
This report analyzes possibilities for increasing revenues for India Post through expanding channeling of financial services. The Indian postal network is among the largest networks in the world in terms of area covered and population served, and constitutes an important mechanism of achieving transportation and communication. Within India Post, the Post Office Savings Bank (POSB) is one of the oldest and largest financial institutions (with largest deposit base) in the country. The key objective of POSB is to provide people living in rural, semi-urban, remote and inaccessible areas of the country with an easy and reliable means of making investments, making remittances and operating savings accounts. It is of strategic importance for POSB to increase market-based revenues so as to gain better control of its market orientation and revenue structure. In addition, though POSB still retains competitive advantages over commercial banks, it will not be long before the competition replicates these advantages. Hence, in order to better leverage the vast network of the post offices and huge customer base, India Post requires evaluating the introduction of a wide range of products and services in the financial services area. This will also lead to improvement of the earnings from savings related products vis-a-vis the total earnings. Banks (e.g. foreign, private banks) lack the network infrastructure to reach underserved segments in semi-urban and rural areas. There is a demand for expansion of financial service offerings by the post office. Some products and services which will help India Post increase its revenues have been identified. Some of these products and services have been introduced as localized initiatives by individual circles. However the experience of these local initiatives needs to be shared and, based on India Post's experience, rolled out to other locations.